TEACHER’S CODE MIXING AND CODE SWITCHING WITHIN EFL ENVIRONMENT - Kamaliah, Adistia Mursyidatul; Amri, M. Misbahul; Laksmi, Ekaning Dewanti (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This current study focused on identifying teacher’s code mixing and code switching within EFL classroom. A descriptive qualitative method was implemented using the concept of code mixing along with code-switching by Muysken and Romaine. The research results additionally demonstrated that code mixing and code switching have been employed in a variety of common classroom circumstances, including introducing the material, discussing the material, posing questions, and concluding the material. The instructor performed two sorts of code mixing: insertion and alternation. Besides, inter-sentential switching along with tag switching or emblematic switching are both kinds of code-switching utilized by the instructor within EFL classroom. As a result, code mixing and code switching pedagogical strategy is highly suggested in bilingual or multilingual classroom to simplify the process of instruction and learning where code mixing along with code-switching are implemented in several typical classroom situations.